AB1357 Iris study: Impact of rheumatic diseases on sexuality. (23rd January 2014) - Cunha-Miranda, L.; Donica, O.; Cardoso, A.; Fernandes, R.
Abstract : Background: Sexual satisfaction is an important issue in everyday life of modern occidental societies. The quality of sexual life, self-esteem and relationship issues might be impaired in patients with chronic rheumatic diseases, due to their poor physical health, pain and functional disability.1 Objectives: The aim of this study is to assess the self-esteem, confidence and relationship satisfaction in patients with rheumatic disease, maintaining sexual activity. Methods: 97 patients were selected in an inpatient questionnaire was applied concerning sexual and socio-demographic information (age, education, marital status, occupation, frequency of sexual activity); the Self-Esteem and Relationship (SEAR) questionnaire: Sexual Relationship domain and Confidence domain; Quality of life was assessed by the Short Form-12 Health Survey (SF-12). Several visual analogue scales (VAS, higher value means higher involvement) were applied for pain, sleep quality, fatigue and two sexual questions: "how far your disease limited your sexual activity" (VAS-SexAct) and "how far your sexuality is important in your relationship" (VAS-Relation). Results: A total of 42 patients were sexually active, 90.5% were female, mean age 56.3±9.8 years [34-77], were distributed by the following diseases: 31% with rheumatoid arthritis (RA), 19% with connective tissue disease (CTD), 16.7% with spondylarthritis, 16.7% with SMED, 11.9% with osteoarthritis (OA) and 4.8% for other diseases. In the frequency of sexual intercourse analysis, 64.3% reported "once or more than once a week". Sex frequency was associated with higher limitation in VAS-Relation and with lower scores in SEAR domains. SEAR global score was 51±21 [11-89], (highest score means greater satisfaction) the sexual relationship domain was 42±25 and confidence domain had an average score of 59±21. The mean SF-12 physical component score (PCS) was 27±7 and the mental component score (MCS) 35±11. Higher limitation in VAS on "how far your disease limited your sexual activity" (VAS-SexAct) was related to lower values in the PCS. Patients with lower sexual satisfaction and confidence had higher MCS impairment. In RA patients, the global SEAR score and all SEAR domains correlated with VAS on "how far your sexuality is important in your relationship" (VAS-Relation); fatigue was associated with major limitations on VAS-SexAct. In patients with CTD, pain was associated to lower confidence; the PCS related to VAS-SexAct and the MCS with VAS-Relation. In SMED patients, SEAR score influenced the SF-12 mental health. In Spondylarthritis, sexual activity limitation by disease affected the quality of sleep; the mental health domain was associated with higher confidence. In patients with OA, the VAS-SexAct was related to pain and to the SF-12 physical health. Conclusions: Our study demonstrates that the SF-12 scores were well below average, with significant impairment of physical and mental health. Mental health was related to confidence domain and to relationship limitation by disease. Sexual satisfaction was influenced by several factors, such as general health, pain, fatigue and sleep quality. It was demonstrated that the disease may be a constraint on relationship and sexual quality of life. References: Sexual function in rheumatic diseases. Araujo DB, Borba EF, Abdo CH, Souza Lde A, Goldenstein-Schainberg C, Chahade WH, Silva CA: Acta Reumatol Port 2010 Jan-Mar;35(1):16-23. Disclosure of Interest: None Declared